2021
DOI: 10.3390/ijms22115820
|View full text |Cite
|
Sign up to set email alerts
|

Cyclovirobuxine D Induced-Mitophagy through the p65/BNIP3/LC3 Axis Potentiates Its Apoptosis-Inducing Effects in Lung Cancer Cells

Abstract: Mitophagy plays a pro-survival or pro-death role that is cellular-context- and stress-condition-dependent. In this study, we revealed that cyclovirobuxine D (CVB-D), a natural compound derived from Buxus microphylla, was able to provoke mitophagy in lung cancer cells. CVB-D-induced mitophagy potentiates apoptosis by promoting mitochondrial dysfunction. Mechanistically, CVB-D initiates mitophagy by enhancing the expression of the mitophagy receptor BNIP3 and strengthening its interaction with LC3 to provoke mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…The understanding of BNIP3 in the regulation of mitophagy is not only to regulate Beclin-1 through BH3 domain to activate autophagy. BNIP3 also activates mitophagy by inducing MMP loss or depolarization and directly interacting with autophagy connecting molecule LC3 (Zeng et al 2021 ; Shi et al 2014 ). When autophagy is activated, the cytoplasmic LC3B-I is cleaved, fatty and inserted into the autophagosome membrane as LC3-II.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of BNIP3 in the regulation of mitophagy is not only to regulate Beclin-1 through BH3 domain to activate autophagy. BNIP3 also activates mitophagy by inducing MMP loss or depolarization and directly interacting with autophagy connecting molecule LC3 (Zeng et al 2021 ; Shi et al 2014 ). When autophagy is activated, the cytoplasmic LC3B-I is cleaved, fatty and inserted into the autophagosome membrane as LC3-II.…”
Section: Discussionmentioning
confidence: 99%
“…It forms a stable homodimer following stress signals and translocates to the outer mitochondrial membrane ( Fu et al, 2020 ; Kubli et al, 2008 ). BNIP3 has a LIR motif at its N-terminal region interaction with LC3, leading to mitophagy ( Zeng et al, 2021 ). NIX is a homology of BNIP3, promoting the selective degradation of mitochondria ( Da et al, 2021 ).…”
Section: Endothelial Mitophagy and Atherosclerosismentioning
confidence: 99%
“…Cyclovirobuxine D (CVB‐D) is the major active component of Buxus microphylla, which is mainly used in the treatment of cardiovascular and cerebrovascular diseases (Bian et al, 2021; Yu, Fang, Lü, Xu, & Lu, 2011). In recent years, more and more evidence has suggested that CVB‐D may have inhibitory effects on various tumors (Lu et al, 2014; Zeng et al, 2021; Zhou et al, 2020). Besides, CVB‐D inhibits CRC cell growth and decreases angiogenesis via the CTHRC1‐AKT/ERK‐Snail signaling pathway, especially microvasculature (Jiang et al, 2020).…”
Section: Natural Anti‐gic Angiogenic Compounds Derived From Plantsmentioning
confidence: 99%